PENAMBAHAN MINYAK GORENG PADA PCM PARAFFIN GUNA MENINGKATKAN KARAKTERISTIK PENYIMPANAN TERMAL PADA MEDIA PENYIMPAN PANAS - Muhammad Katibi Vanhas; Nasrul Ilminafik; Rahma Rei Sakura; Andi Sanata; M Nurkoyim Kustanto; FX Kristianta (STATOR: Jurnal Ilmiah Teknik Mesin, 2022)
The number of energy demand these days is very high. This shows the need for new inonovation to solve the problem of energy needs, one of which is the use of Phase Change Material (PCM) as a heat exchanger material. The purpose of this research is to know the characteristics of PCM with addition cooking oil and paraffin. The percentage of cooking oil and paraffin are 30%, 40%, and 50% of total volume. The research was start with heating process during 1 hours with temperature ± 25oC. Result of this research shows PCM paraffin - cooking oil with 50% mixture is the best cooling speed PCM, next is PCM paraffin - cooking oil 40% mixture, and the last is PCM paraffin - cooking oil with 30% mixture. On the cooling process, the 30% cooking oil mixture can hold the temperature longers than the other, while the 40% cooking oil mixture has second position, and the last is 50% cooking oil mixture. The conclusion is the addition of cooking oil can improve thermal conductivity of PCM.